Synthesis and characterization of noble metal–titania core–shell nanostructures with tunable shell thickness - Bartosewicz, Bartosz; Michalska-Domańska, Marta; Liszewska, Malwina; Zasada, Dariusz; Jankiewicz, Bartłomiej J. (Beilstein Journal of Nanotechnology, 2017)
Core–shell nanostructures have found applications in many fields, including surface enhanced spectroscopy, catalysis and solar cells. Titania-coated noble metal nanoparticles, which combine the surface plasmon resonance properties of the core and the photoactivity of the shell, have great potential for these applications. However, the controllable synthesis of such nanostructures remains a challenge due to the high reactivity of titania precursors. Hence, a simple titania coating method that would allow better control over the shell formation is desired. A sol–gel based titania coating method, which allows control over the shell thickness, was developed and applied to the synthesis of Ag@TiO2 and Au@TiO2 with various shell thicknesses. The morphology of the synthesized structures was investigated using scanning electron microscopy (SEM). Their sizes and shell thicknesses were determined using tunable resistive pulse sensing (TRPS) technique. The optical properties of the synthesized structures were characterized using UV–vis spectroscopy. Ag@TiO2 and Au@TiO2 structures with shell thickness in the range of ≈40–70 nm and 90 nm, for the Ag and Au nanostructures respectively, were prepared using a method we developed and adapted, consisting of a change in the titania precursor concentration. The synthesized nanostructures exhibited significant absorption in the UV–vis range. The TRPS technique was shown to be a very useful tool for the characterization of metal–metal oxide core–shell nanostructures.
Keywords: Ag@TiO2; Au@TiO2; core–shell nanostructures; titania coating; titanium dioxide; tunable resistive pulse sensing